2010
DOI: 10.1007/s11258-010-9818-6
|View full text |Cite
|
Sign up to set email alerts
|

What are the effects of substrate and grass removal on recruitment of Acacia mellifera seedlings in a semi-arid environment?

Abstract: Acacia mellifera is one of the most important encroaching woody plants in southern African savannas. Previous studies found that this species encroaches far more readily on rocky areas than on sandy substrates, although it grows larger on sandy substrates. Rocky substrates are known to retain more water than sandy substrates, which may be of vital importance during recruitment in semi-arid and arid environments. A number of studies have also indicated that competition with grasses may reduce the recruitment an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
58
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(67 citation statements)
references
References 27 publications
7
58
0
2
Order By: Relevance
“…Grass competition emerged as the major factor limiting basal diameter growth and branch production inside glades, and to a lesser degree, it also limited growth outside glades. These results support previous studies in our system (Riginos and Young 2007;Riginos 2009) and other savannas (Knoop and Walker 1985;van der Waal et al 2009;Cramer et al 2010;Ward and Esler 2011) which found that grass competition can significantly restrict tree growth and recruitment. In a pot experiment, van der Waal et al (2011) went a step further by showing that competition between grasses and trees was more intense when plants were grown in glade-derived, nutrient-rich soil.…”
Section: Impacts Of Grasses and Browsingsupporting
confidence: 93%
“…Grass competition emerged as the major factor limiting basal diameter growth and branch production inside glades, and to a lesser degree, it also limited growth outside glades. These results support previous studies in our system (Riginos and Young 2007;Riginos 2009) and other savannas (Knoop and Walker 1985;van der Waal et al 2009;Cramer et al 2010;Ward and Esler 2011) which found that grass competition can significantly restrict tree growth and recruitment. In a pot experiment, van der Waal et al (2011) went a step further by showing that competition between grasses and trees was more intense when plants were grown in glade-derived, nutrient-rich soil.…”
Section: Impacts Of Grasses and Browsingsupporting
confidence: 93%
“…There was no effect of grass competition on RGR L of all species excluding A. nigrescens and Schotia brachypetala, RGR D of A. sieberiana, and LP of Strychnos spinosa and Combretum apiculatum. It is widely understood that grass competition is a fundamental hindrance to savanna tree sapling establishment (Riginos and Young 2007, Kambatuku et al 2011, Ward and Esler 2011, Grellier et al 2012. We further note that the grasses in our experiment were relatively young plants; older, established grasses would likely present a greater constraint on tree establishment (Jurena and Archer 2003, Ward 2005, Messier et al 2009).…”
Section: Notesmentioning
confidence: 70%
“…However, consistent with the findings of Vadigi and Ward (2012) for Acacia saplings, we found no nutrient effect on sapling survival in any species. Grass competition, identified as the greatest hurdle for sapling survival by Grellier et al (2012) and Ward and Esler (2011), also did not have an effect on sapling survival. Perhaps, in humid savannas, other environmental factors such as temperature, fire and herbivory play a more influential role in savanna sapling survival (Shaw et al 2002, Hoffmann and Solbrig 2003, Sharam et al 2006, Chidumayo 2008, Gignoux et al 2009).…”
Section: Sapling Survivalmentioning
confidence: 85%
See 1 more Smart Citation
“…Heavy grazing in mesic savannas reduces fuel load through consumption and trampling, thereby reducing fire frequency and more significantly fire intensity [1,31,36,44,53]. Overgrazing has also been reported to reduce the effect of grass competition on tree seedlings and saplings, as a dense grass layer can negatively affect tree growth and survival [54][55][56]. Long-term grazing trials in both mesic and arid systems have consistently reported increases in the density of woody plants over 5-40 year periods of observation [52].…”
Section: Grazers and Browsersmentioning
confidence: 99%